CHARACTERISTICS OF HYPOSPADIAS CASES IN SANGLAH GENERAL HOSPITAL, BALI-INDONESIA: A DESCRIPTIVE STUDY - Duarsa, Gede Wirya Kusuma; Nugroho, Teguh Dwi (BALI MEDICAL JOURNAL, 2016)
Background: Hypospadias is one of the most common congenital anomalies. The purpose of this study is to assess the characteristics of hypospadias patients in Sanglah General Hospital, and the type of hypospadias repair and the outcome. Methods: The data is collected retrospectively from the hypospadias patients’ medical records who undergone a hypospadias repair between January 2009 to April 2012. The data is analyzed descriptively to describe the characteristics of hypospadias patients, the procedures taken, and the outcomes. Results: From 42 patients, type of hypospadias are 33.3% (n=14) penoscrotal; 21.4% (n=9) scrotal; 14.3% (n=6) corona; 26.2% (n=11) penile; 2.4% (n=1) subcoronal; 2.4% (n=1) and perineal. Chordee was present in 67.9% cases (n=36), and cryptorchidism present in 3.7 % case (n=2). The urethroplasty techniques applied: TIP 55.6% (n=15); Duckett Preputial Island Flap 14.8% (n=4); MAGPI 14.8% (n=4); 14.8% (n=4) two stages urethroplasty. Complication rate of Duckett is 50% (n=2) urethra cutaneous fistula; MAGPI 25% (n=1) meatal stenosis; TIP 20% (n=3), 2 urethrocutaneous fistula, 1 urethral stricture; 2 stages urethroplasty 0% (n=0). Conclusion: The findings suggest a different frequency of the proportion of the type of hypospadias in this study when compare to the readily available literature. The age of the patients undergone hipospadias repair was higher compare to other studies. TIP technique was the most preferred in Sanglah Hospital.
Keywords: congenital; anomalies; cryptochidism; urethra.